Decoration of Ceramic Tile by Outsible Materials, as a Universal Method of Treating Children under the Conditions of Hospital - A. Boyko, Yu.; P. Dragunova, E. (International Journal of Engineering and Technology, 2018)
A modern person, being subjected to ever-increasing loads, is forced to constantly think about the preservation of health and efficiency. Consultative and treatment centers have gradually become important objects of maintaining health, in which people spend quite a large part of their time, starting from the first days of life. Unfortunately, in recent years, a significant proportion of patients at medical centers and clinics have been composed of children of different age groups, as the most vulnerable part of society carrying the burden of the social life of a metropolis. This article analyzes the possibility of using overglaze painting to create visual images of any degree of complexity on the surface of ceramic tiles when designing medical centers for treating children.Â